An Increasing Berry Fruit Production (Antidesma Bunius L. Spreng) With Hybrid Fertilizer Processing Based On Coconut Water Fragmentation - Hafiz Ahmad (Jurnal Scientia, 2024)
Berry fruit plants are plants that are usually planted in open places or in secondary forests. Berry fruit plants can be cultivated vegetatively, namely by cuttings and being treated with fermented P fertilizer and coconut water. The aim of this research was to determine the effectiveness of fermented P fertilizer and coconut water on the growth of berry fruit plant cuttings. This research using the Factorial Randomized Block Design (RAK) method with 2 factors, namely fermented P fertilizer and coconut water. Fermented P fertilizer treatment consists of 4 levels, namely M0= 0 ml/plot, M1= 200 ml/plot , M2= 300 ml/plot and M3= 400 ml/plot. The coconut water treatment consisted of 4 levels, namely P1= 50 ml/liter of water, P2= 100 ml/liter of water, P3= 150 ml/liter of water and P4= 200 ml/liter of water. The parameters observed were the age at which shoots emerged (days), shoot length (cm), number of shoots (stems) and shoot diameter (mm). This paper described a results showed that fermented P fertilizer had no significantly different effect on the parameters of shoot emergence age, shoot length, number of shoots and stem diameter. Providing coconut water had no significantly different effect on the parameters of shoot emergence age, shoot length, number of shoots and stem diameter. The interaction between fermented P fertilizer and coconut water did not have a significantly different effect on all parameters.